Three Models of English Morphology - Bram, Barli (LLT Journal: A Journal on Language and Language Teaching, 2012)
This paper explores models of English morphology, namely Item and Arrangement (IA), Item and Process (IP), and Word and Paradigm (WP), which can be used to analyze morphological data, particularly word formation involving prefixes and suffixes. Sample data, consisting of complex words or words having more than one morpheme, were analyzed using the three models to discover their strengths and shortcomings. In order to find out the differences between the three models of morphology, it is important that the current writer should examine strategies for distinguishing between derivational affixes and inflectional ones. There exist three advantages if morphologists know very well the three models of English morphology. First is that IA fails to display a clear sequence of the item and arrangement when dealing with some irregular plural nouns and irregular past tense. Second is that IP offers a better solution to irregular plural nouns, such as mice and men. Third is that WP appears to be the most efficient model when dealing with inflectional morphology.